Constitutive modeling and mechanical behavior prediction of biodegradable polymers during degradation - André Vieira (2015)
A large range of biodegradable polymers has been used to produce implantable medicaldevices, such as suture fibers, fixation screws and soft tissue engineering devices. Apartfrom biological compatibility, these devices should also be functional compatible andperform adequate mechanical temporary support during the healing process. Themechanical behavior of biodegradable polymers is known to be rate dependent and toexhibit hysteresis upon cyclic loading. On the other hand, ductility, toughness andstrength of the material decay during hydrolytic degradation. Continuum basedmechanical models can be used as dimensioning tools for biodegradable polymericdevices, since they enable to predict its mechanical behavior in a complex load andenvironment scenario, during the hydrolytic degradation process.The existing models can be divided into two categories: the time-dependent models andthe time-independent models. Linear elastic or non-linear elastic models, such as elastoplasticor hyperelastic models, can simulate the time-independent response, whichcorresponds to the relaxed configuration and represent the relaxed state. However, theseapproaches neglect the time-dependent mechanical behavior. To consider timedependency, dissipative elements must be used in the model formulation.A revision of the three-dimensional constitutive models generally used for polymers ispresented in this chapter. These models are based on the concept of networks, combiningelastic, sliding and dissipative elements, in order to simulate the time-dependentmechanical behavior, although neglecting changes in the properties of the material duringhydrolytic degradation process. Thus, some of these models were recently adapted toaddress the hydrolytic degradation process. A common method consists on becomingsome of the material model parameters dependent on a scalar variable, which expressesthe hydrolytic damage.Furthermore, the advantages and limitations of the models arediscussed, based on the correlation between predictions and experimental results of ablend of polylactic acid and polycaprolactone (PLA-PCL), which include monotonictensile tests at different strain rates and quasi-static cyclic unloading-reloading.